2017
DOI: 10.1016/j.envint.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of urinary flame retardant concentration among pregnant women

Abstract: Background Organophosphate compounds are commonly used in residential furniture, electronics, and baby products as flame retardants and are also used in other consumer products as plasticizers. Although the levels of exposure biomarkers are generally higher among children and decrease with age, relatively little is known about the individual characteristics associated with higher levels of exposure. Here, we investigate urinary metabolites of several organophosphate flame retardants (PFRs) in a cohort of pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
93
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 47 publications
11
93
2
Order By: Relevance
“…Our findings generally suggest that women with higher weight or greater BMI tend to have higher concentrations of BCEP, BDCPP, and DPhP in their urine than lighter women. This is consistent with one prior study of pregnant women in which women who were overweight or obese before pregnancy tended to have higher urinary concentrations of BDCPP and DPhP than women with normal pre-pregnancy body mass index [25]. One possible explanation is that TPhP, the parent PFR of DPhP, has been used as a plasticizer (potentially as a substitute for dibutyl phthalates) in nail polish [38], and may be used as a plasticizer or phthalate substitute in other personal care products.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings generally suggest that women with higher weight or greater BMI tend to have higher concentrations of BCEP, BDCPP, and DPhP in their urine than lighter women. This is consistent with one prior study of pregnant women in which women who were overweight or obese before pregnancy tended to have higher urinary concentrations of BDCPP and DPhP than women with normal pre-pregnancy body mass index [25]. One possible explanation is that TPhP, the parent PFR of DPhP, has been used as a plasticizer (potentially as a substitute for dibutyl phthalates) in nail polish [38], and may be used as a plasticizer or phthalate substitute in other personal care products.…”
Section: Discussionsupporting
confidence: 92%
“…Both BDCPP and DPhP have been frequently detected in the urine of mothers [13, 14, 24, 25], young children [12, 13, 24], and the general population [1012, 1518]. Urinary concentrations of BDCPP and DPhP observed in our study were generally consistent with those previously observed among pregnant women [14, 25] (Additional file 1: Table S10).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Metabolites of TDCIPP (BDCIPP) and TPHP (DPHP) were detected in 77% and 79% of urine samples. Compared to PFR exposure assessed in 349 pregnant women from North Carolina in the early 2000s (Hoffman et al 2017), the median (max) PFR metabolite levels in the CHAMACOS cohort were lower (BDCIPP: 0.4 (53.1) ng/ml, DPHP: 0.9 (54.1) ng/ml) than the North Carolina study (BDCIPP: 1.9 (140) ng/ml, DPHP: 1.3 (112) ng/ml). The relatively high urinary PFR levels reported by Hoffman et al 2017 were not expected as sample collection for the study occurred before the phase out of the penta-BDE flame retardant mixture (Stapleton et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Literature (Butt et al, 2014;Hoffman et al, 2015;Butt et al, 2016;Hoffman et al, 2017) Additional biomonitoring studies from the USA summarised in a recent review Review ASSESSMENT The lack of data on occurrence is most likely the result of the complex and variable composition of the substance and its commercial products. Limited analyses of commercial products indicate that substances containing only one isopropyl group are major constituents.…”
Section: Hydrolysis Of Ippp Considered Negligible Under Most Environmmentioning
confidence: 99%